Current Nucleic Acid Extraction Methods and Their Implications to Point-of-Care Diagnostics. (12th July 2017) - Ali, Nasir; Rampazzo, Rita de Cássia Pontello; Costa, Alexandre Dias Tavares; Krieger, Marco Aurelio
Abstract : Nucleic acid extraction (NAE) plays a vital role in molecular biology as the primary step for many downstream applications. Many modifications have been introduced to the original 1869 method. Modern processes are categorized into chemical or mechanical, each with peculiarities that influence their use, especially in point-of-care diagnostics (POC-Dx). POC-Dx is a new approach aiming to replace sophisticated analytical machinery with microanalytical systems, able to be used near the patient, at the point of care or point of need . Although notable efforts have been made, a simple and effective extraction method is still a major challenge for widespread use of POC-Dx. In this review, we dissected the working principle of each of the most common NAE methods, overviewing their advantages and disadvantages, as well their potential for integration in POC-Dx systems. At present, it seems difficult, if not impossible, to establish a procedure which can be universally applied to POC-Dx. We also discuss the effects of the NAE chemicals upon the main plastic polymers used to mass produce POC-Dx systems. We end our review discussing the limitations and challenges that should guide the quest for an efficient extraction method that can be integrated in a POC-Dx system.